Perspektif Pembinaan Tim Puslatda Wushu Sanshou Jawa Timur dalam Persiapan Pekan Olahraga Nasional (PON) yang Ke-XIX Tahun 2016 di Jawa Barat - sofiana, efi dian (JOSSAE (Journal of Sport Science and Education), 2018)
Wushu Sanshou is a martial sport of China and background research is to determine the development of athlete puslatda wushu sanshou East Java. National sport week is a national sport festival held every 4 years that followed by provience exist in Indonesia. Almost all kind of sportsare contested in this festival including Wushu sanshou. The purpose of this study is to find perspective management team puslatda wushu sanshou east java in preparation national sports that XIX years 2016 in West Java.To improve their performance athletes of course affected many factors among them: the athletes, coach, organization facilities, nature about, participation government. The research is qualitative study by using the method descriptive.The collection locations data was undertaken in school the national academy surabaya star who is also a place of exercise training for athletes puslatda wushu sanshou east java.The subject of study was chairman of the wushu, coach, and athletes puslatda wushu sanshou East Java. The results of data processing conducted using data analysis through interviews with the subject of study was chairman of, coach, athletes puslatda wushu sanshou east java. The conclusion of the research is guidance on a KONI East Java good, complete infrastructure facilitues, an exercise programe that has been programmed in a systematic and planned from 2013 until 2016. In addition there is also a supporting factor inhibiting factor is the lack of good stewrdship less compact in which the team of administrators athletes and coaches becomes harmonious relationship